2001
DOI: 10.1111/j.1348-0421.2001.tb01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness between the Coagulase Gene 3′‐End Region and Coagulase Serotypes among Staphylococcus aureus Strains

Abstract: Abstract:The 3'-end region of the coagulase gene from 22 strains of Staphylococcus aureus including 10 standard serotype strains was sequenced, and five suhgroups with 4-8 tandem repeating units were distinguished among the tested strains. Phylogenetic analysis of the 3'-end region of the coagulase gene indicated that strains belonging to the same serotype were clustered in the same branch. A phylogenetic tree of the deduced amino acid sequences revealed that the C-terminal region might not be responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…The sizes of the products ranged from 350 to 917 bp in increments of 81 bp, reflecting the number of 81-bp repeat units contained in the coa gene after digestion with AluI and this allowed the differentiation of 31 coa-RFLP types and was able to distinguish them from each other confirming the sensitivity of coa/RFLP in differentiation [23]. This difference between our results and other studies [23,28] might be due to our small sized samples or due to differences in MRSA strains as mentioned in previous studies [6,16,31] who reported that S. aureus strains of the same coagulase serotype can be differentiated by Alu restriction and nucleotides sequence analysis of coa gene. In the current study, nucleotides sequence variability of tandem repeat region in coa-gene PCR products was able to discriminate the examined unclassified isolates.…”
Section: Discussionsupporting
confidence: 65%
“…The sizes of the products ranged from 350 to 917 bp in increments of 81 bp, reflecting the number of 81-bp repeat units contained in the coa gene after digestion with AluI and this allowed the differentiation of 31 coa-RFLP types and was able to distinguish them from each other confirming the sensitivity of coa/RFLP in differentiation [23]. This difference between our results and other studies [23,28] might be due to our small sized samples or due to differences in MRSA strains as mentioned in previous studies [6,16,31] who reported that S. aureus strains of the same coagulase serotype can be differentiated by Alu restriction and nucleotides sequence analysis of coa gene. In the current study, nucleotides sequence variability of tandem repeat region in coa-gene PCR products was able to discriminate the examined unclassified isolates.…”
Section: Discussionsupporting
confidence: 65%
“…The seven S. aureus strains were as follows: strain 104 (type I), Stp-28 (type IV), no. 55 (type V), Stp-12 (type VI), Ku (type VIII), 17573 (type IX), and 19 (type X) (23,45). To investigate the genetic relatedness between serotypes of coa and genetic backgrounds of S. aureus strains, we selected nine strains whose ribotypes had been determined and sequenced their coa.…”
Section: Methodsmentioning
confidence: 99%
“…The repeat regions comprising 27-amino-acid tandem repeats are highly polymorphic in the number of repeats. Although the serotypes do not correlate with the polymorphism of 27-amino-acid tandem repeats (23), both the N-terminal region and the C-terminal region have been used for S. aureus differentiation by analyzing their diversity using amplified DNA fragments and subsequent restriction fragment length polymorphism analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coagulase typing, i.e., the neutralization of S. aureus coagulation of citrate-plasma with specific antiserum, has been used to distinguish 10 different serological Coa types (17). Coa types have also been analyzed by DNA sequencing, which revealed significant variation within coa sequences for the D12 domain and little variation for the linker and repeat regions, respectively (44).…”
mentioning
confidence: 99%